Faktor - Faktor yang Berhubungan dengan Keberhasilan Program Penanggulangan TBC - Purwanto, Medy; Kurniati, Dwi Maya; Nurasbon, Nurasbon; Irdan, Irdan (JURNAL KESEHATAN TERAPAN, 2025)
Tuberculosis (TB) continues to stand as a pressing challenge in global public health. Success in identifying new cases and completing treatment cycles serves as a key indicator in measuring the effectiveness of TB control efforts. When treatment fails, not only does it heighten the risk of transmission to others, but it can also give rise to drug resistance, often referred to as multidrug-resistant TB (MDR TB). This study was designed to explore the relationship between patients’ knowledge, the role of Treatment Supervisors (PMOs), and internal motivation with the success of TB control efforts at Sekayu Regional Hospital in 2018. An analytical survey approach was adopted using a cross-sectional design, involving 52 respondents. The findings revealed statistically significant associations between knowledge (p = 0.005), PMO involvement (p = 0.000), and motivation (p = 0.031) and the effectiveness of the TB program. These results highlight the essential role of healthcare workers, especially in providing education and counseling, to empower communities in preventing the early spread of infectious diseases.